(3GdeYGQas - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s ((3Ydi Hf eMeO Hf ZGjI Gddg s)
(3ChdgG (B:s
(3bGd GdTjN GdQFjS CHhYdi Hf YHOGddg Hf SjfG aUd hdeG cGfJ GdcJH ddeHJOFjf hGdeJCNQjf s
(3BNQgG (B:s
(3CTHGg gPg GdQDjG cKjQI bO GSJNQLgG GdJLGQH Ydi eQ GdCjGe s
(3Vef eLehY , JQJjHgG (B: (3ef U (B44 - (3U(B86s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3GdadSaI hGdefWbs